Wawangsalan Bahasa Sunda (Jurnal Bahasa, 2010)
Wawangsalan in Sundanese is the arrangement of words into riddles, similar to wawangsalan in Cirebonese literature. In Sundanese literature, wawangsalan is categorised as a form of sisindiran. Sisindiran is a sub-genre of poetry similar to pantun in Malay literature. Sisindiran grew and flourished in Sundanese communities in general. The word sisindiran is derived from the word "sindir" ("menyindir") meaning to say something indirectly or implicitly. Sisindiran is a form of Sundanese traditional poetry the structure of which consists of metaphoric and thematic lines. Sisindiran, originally Sundanese literary genre, existed long before the arrival of Islam. This paper focuses on wawangsalan tatarucingan, a type of wawangsalan that consists of two lines: the first being a riddle and the second being the means of giving the listener a clue to guess the answer to the first line. The implicit message could be a rebuke, a reminder, a request, or an indirect description of one`s character.Keywords: wawangsalan, riddle, sisindiran